PENGARUH METODE OUTDOOR LEARNING TERHADAP ENJOYFULL SISWA PADA MATERI PERMAINAN TRADISIONAL KELAS V SDN 113 PALEMBANG - WULANDARI, AYU; ARYANINGRUM1, KIKI; UTOMO, BUDI (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Students who do not enjoy it are not optimal during the learning process, but in the class V SDN 113 Palembang Enjoyfull level students are still low because of the use of monotonous methods. Therefore, this study aims to determine the effect of outdoor learning methods on student enjoyfulls on traditional game material in class V. The application of outdoor learning methods is expected to increase student enjoyfull students while studying. This type of research design is true experimental design with research samples, namely class V.B students as the experimental class and class V.C as the control class. The results of the data analysis using the Man Whitney u test showed a significant value of 0.004 (less than 0.05), so it could be concluded that H0 was rejected and Ha was accepted. These results indicate a significant difference in student enjoyfull levels between the experimental class and the control class. The implication of this study is that the outdoor learning method is effective for creating an atmosphere that is enjoyful, so it can be used as an innovative alternative to the teacher.